A STUDY OF STUDENTS WITH DYSCALCULIA AND THEIR MATHEMATICAL ABILITIES AT PRIMARY SCHOOLS IN KARAIKUDI - Jeya, A Adaikala; Albina, A Pio (PEOPLE: International Journal of Social Sciences, 2019)
Education is considered to be a key factor for the growth and process of any society. Mathematics Education is an important component of school Education. Learning difficulties is a major contributing factor for the children in schools, which requires immediate concern. Dyscalculia refers to an incurable difficulty in learning and understanding Mathematics. Primary School students find these difficulties in learning of number concepts and basic arithmetic. The study under investigation is to find out children who are affected by dyscalculia in the schools of karaikudi. The investigator proposes to use Survey Method for this study. Population for the study is Primary school students in karaikudi. The random sampling technique was used for this study. The sample is 100 primary school students in karaikudi. The tool for the study is adopted screening tool for identifying the dyscalculic students. The study revealed 9% students of the primary school in karaikudi were found to be dyscalculia. Hence identifying the dyscalculic students and giving them the necessary intervention programmes to improve their learning difficulties in Mathematics and it is the need of the hour.A